Organized Civil Servants Public Employer-Employee Relations in California. - Crouch, Winston W. (University of California Press, 2020)
In the early 1960s, the militant demands of some organizations of state and local government employees to participate in decisions about compensation and conditions of employment challenged many established concepts of public administration. A series of strikes revealed a lack of public policy and administrative techniques to cope with the problems presented by aggressive and innovative groups of public employees. Although civil servants had been organized in.